Space electronic reconnaissance : localization principles and technologies - Guo, Fucheng, 1975- (Singapore : John Wiley & Sons Inc., 2014)
"Presents the theories and applications of determining the position of an object in space through the use of satellites"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Space surveillance; Electronic surveillance; Aerial reconnaissance; TECHNOLOGY & ENGINEERING / Electronics / General; Aerial reconnaissance; Electronic surveillance; Space surveillance; Electronic books; Electronic books